LA FAMIGLIA CRISTIANA – IL FONDAMENTO DELLA VOCAZIONE - HLOVA, Ivan (Studia Universitatis Babeș-Bolyai Theologia Catholica, 2018)
The Christian Family – the Foundation of the Vocation. Family is a deep communion of life and love, established by the Creator and regulated by His laws. It is the strongest bond that can exist between a woman and a man. The concept of family is closely connected with its monogamous nature. In the sacrament of marriage, spouses receive a grace from Christ, which is intended for the perfecting of love and for strengthening their indissoluble unity. Nowadays, marriage is experiencing a crisis. It would be worth showing the marriage not only as a covenant, communion or institution, but as a vocation (the act of summoning which is connected with the mission of fulfilling a specific task). The essence of the Christian vocation deriving from baptism; is a dialogue between the freedom of God and of the man, preceded by the choice of a person and commissioned by his mission. It is the sacramental marriage that is the way to connect with God, follow Christ, which is the most appropriate way for a married couple to walk to holiness. Therefore, an important message for the contemporary is to show marriage as a vocation that is addressed to two people and should be accepted and implemented by them. Familia creștină – fundamentul vocației. Familia este o comuniune profundă de viață și iubire, stabilită de Creator și reglementată prin legile sale. Este cea mai puternică legătură care poate exista între un bărbat și o femeie. Conceptul de familie este strâns legat de natura sa monogamă. În Taina căsătoriei, soții primesc un har de la Cristos, care este destinat să perfecționeze iubirea și să consolideze uniunea lor indisolubilă. În zilele noastre, căsătoria trece printr-o criză. Este util să arătăm căsătoria nu doar ca pe un legământ, comuniune sau instituție, ci ca pe o vocație (actul de a fi chemat, legat de misiunea de a îndeplini o anumită sarcină). Esența vocației creștine este rezultatul botezului sfinților. Există un dialog între libertatea lui Dumnezeu și a omului, precedată de alegerea unei persoane și de încredințarea unei misiuni. Căsătoria sacramentală este calea pentru a fi în legătură cu Dumnezeu, a-l urma pe Cristos, ceea ce reprezintă calea cea mai adecvată pentru un cuplu căsătorit pentru a ajunge la sfințenie. Ca urmare, un mesaj important pentru contemporani este să arătăm căsătoria ca pe o vocație care este adresată către două persoane și care trebuie acceptată și pusă în aplicare de ele. Cuvinte-cheie: familie, căsătorie, vocație, Biserică, sacrament, comunitate, căsătorit, dragoste.